Employability Model Evaluation of Engineering Technology Graduates: A PLS-SEM Approach - Long, Pham Duc; Nga, Nguyen Thuy; Thuy, Tang Thi; Thuy, Nguyen Thi Ha (VNU Journal of Science: Education Research; Vol 40 No 4DO - 10.25073/2588-1159/vnuer.4973, 2024)
The paper evaluated a four-construct employability model for engineering technology graduates in the context of globalisation and job insecurity. Four constructs of fifty-two items in the model involve i) Technical knowledge; ii) Technical skills; iii) Generic skills; and iv) Attitude and other attributes. Survey data were collected from 153 industry employers that used engineering technology graduates and analysed using a partial least-squares structural equations modelling (PLS-SEM) technique. Measurement and structural models were assessed to examine the quality of outer and inner models. The findings showed that the measurement model was reliable. Five items were removed due to internal consistency reliability problems. The results of re-performing the PLS-SEM algorithm confirmed that the adjusted model of four constructs and forty-seven items was reliable. The structural model assessment recorded the fit of inner models, with eight inner models having statistical significance. The research contributes to developing highly qualified engineers by confirming the tailored employability model for graduates of engineering technology disciplines. Future studies could apply the model to measure the employability of engineering technology graduates from specific higher education institutions in Vietnam.